(untitled) (Research, Society and Development, 2020)
Water quality is an important tool to support the planning and management of water resources. This article has as its main objective to evaluate changes in the quality of the surface waters of the Timbó stream as a function of flow in an experimental watershed located in São Cristóvão (SE), northeastern Brazil. Four sampling campaigns were carried out in 2018 to evaluate pH, dissolved oxygen, electrical conductivity, total dissolved solids, turbidity and temperature at three collection points. Data on land use and occupation and the flow of the Timbó stream were also obtained. The land use and occupation survey indicated that 51% of the total area of the microbasin is occupied by forests and that 49% is composed of pasture, undergrowth and exposed soil. The correlation analysis identified a strong correlation (p-value <0.05) between the studied parameters, with an emphasis on a direct relationship between Q and TUR (r = 0.9) and Q and O (r = 0.6) and an inversely proportional relationship between TDS and CE (r = -0.8), confirming the results of a principal component analysis, where the parameters contributing the most to the quality of the investigated water resource were CE, TDS, OD and turbidity.